Interactive Music-Based Learning: Exploring the Impact of Lingoclip Application on Listening Skill Enhancement - Kau, Magvirah El Walidayni; Badu, Helena; Malabar, Fahria; Monoarfa, Alya (Riwayat: Educational Journal of History and Humanities, 2025)
Listening is one of the most challenging skills for students to master, and innovative media are required to make the learning process more engaging and effective. This study aims to identify students perceptions of using the LingoClip application as a medium for learning listening. The research employed a descriptive qualitative design involving students from SMP Bone as participants. Data were collected through interviews and analyzed using thematic analysis. The findings revealed five emerging themes. Students perceived LingoClip as a fun and enjoyable learning medium that created a relaxed and positive atmosphere. The application was considered easy to use, with clear audio quality and supporting visual features that facilitated comprehension. Students demonstrated high motivation and confidence in using LingoClip and expressed a desire to reuse it in future lessons. However, some reported technical issues such as limited internet access and small screen sizes. Overall, LingoClip positively influenced students learning experiences by fostering enjoyment, motivation, and confidence, demonstrating its potential as an effective tool for listening instruction.